A mother's guide to raising herself: what parenting taught me about life, faith, and myself - Bragg, Sarah (Zondervan, 2021)
"Raising great kids starts with raising yourself well, yet it's all too easy to lose our identity in the daily struggle of motherhood. Popular podcaster and mom Sarah Bragg offers refreshing wisdom and shame-free practical help to becoming your best and truest self in A Mother's Guide to Raising Herself"--